The Relationship Between Academic Stress Levels and Nutrient Consumption Levels with Nutritional Status of UNESA Faculty of Engineering Students During Online Learning - Rastamadya, Syaifuddin; Sulandjari, Siti (Jurnal Gizi dan Kesehatan Nusantara, 2022)
The Policy for the Implementation of Restrictions on Community Activities (PPKM) resulted in the changing pattern of learning in college from face-to-face learning to online learning and caused academic stress problems for students, especially in the science and technology study program. Academic stress experienced by students during online learning becomes suspected of causing changes in energy needs and levels of student nutrient consumption. This study aims to determine the relationship between levels of academic stress and nutrient consumption with the nutritional status of engineering faculty students at UNESA during online learning. This type of research is a correlational study with a cross-sectional analytic study design. Sampling used the purposive sampling method. Data was collected using an online questionnaire method via google form and direct measurement for the subject’s weight and height. The data was processed by the Rank Spearman Test using SPSS version 25 software. The results showed no relationship between levels of academic stress and nutrient consumption with nutritional status (p-value>0.05). Based on the bivariate analysis conducted, the results showed that there was no significant relationship between the level of academic stress (p-value: 0.557), the level of energy consumption (p-value: 0.341), the level of protein consumption (p-value: 0.453), the level of fat consumption (p-value: 0.410) and the level of carbohydrate consumption (p-value: 0.129) with nutritional status in students of the Faculty of Engineering UNESA during online learning. There is no relationship between the level of academic stress, the level of energy, protein, fat, and carbohydrates consumption with the nutritional status of the students of the Faculty of Engineering UNESA during online learning.